1970
DOI: 10.1002/1097-4679(197010)26:4<430::aid-jclp2270260405>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Internal vs. external control time perspective and delay of gratification of high and low ego strength groups

Abstract: PROBLEM concerning ego strength emphasizes lack of agreement as to what constitutes ego strength and the poor interrelationships obtained between various measures designed to assess it. This raises a question whether any consistent differences can be observed between groups differing in ego strength. This study compares high and low ego strength groups on three measures: Internal vs. External Control, Time Perspective, and Delay of Gratification. Previous studies('. report a stronger belief in Internal Control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…A. Greene & DeBacker, 2004;Miller & Brickman, 2004;Phalet, Andriessen, & Lens, 2004;Simons et al, 2000;Simons et al, 2004), delay of gratification (Bembenutty & Karabenick, 2004;Shybut, 1970), delinquency (Oyserman & Markus, 1990a, 1990b, and academic achievement (e.g., Anderman, Anderman, & Griesinger, 1999;de Volder & Lens, 1982;Groth, 1973;Honora, 2002;Shell & Husman, 2001;Teahan, 1958). However, the emphasis on the future has resulted in a relative neglect of the potential importance of adolescents' past and present TPs.…”
mentioning
confidence: 99%
“…A. Greene & DeBacker, 2004;Miller & Brickman, 2004;Phalet, Andriessen, & Lens, 2004;Simons et al, 2000;Simons et al, 2004), delay of gratification (Bembenutty & Karabenick, 2004;Shybut, 1970), delinquency (Oyserman & Markus, 1990a, 1990b, and academic achievement (e.g., Anderman, Anderman, & Griesinger, 1999;de Volder & Lens, 1982;Groth, 1973;Honora, 2002;Shell & Husman, 2001;Teahan, 1958). However, the emphasis on the future has resulted in a relative neglect of the potential importance of adolescents' past and present TPs.…”
mentioning
confidence: 99%
“…The findings have demonstrated that although the world cannot be neatly divided into externals and internals, a high degree of internality correlates closely with personal well-being. At least four studies revealed that persons with a high belief in internal control are more confident and have higher levels of self-esteem (Abramowitz, 1969;Fish & Karabenick, 1971;Hersch & Scheibe, 1967;Platt & Eisenman, 1968;Reznikoff, Bridges, & Hirsch, 1972;Roberts, 1971;Shybut, 1970;Warehime & Woodson, 1971). One study found internals to be less prone to depression (Abramowitz, 1969), and another reported them to be less suicide prone (Williams & Nickels, 1969).…”
Section: Internality Correlationsmentioning
confidence: 99%